Electronic structure of Cu100−xZrx (x = 40, 50, 60) metallic glasses. (5th October 2015) - Yang, Weiming; Liu, Haishun; Wang, Qianqian; Wei, Zhining; Xue, Lin; Dun, Chaochao; Zhao, Yucheng; Chang, Chuntao; Shen, Baolong
Graphical abstract: Highlights: Investigation of the electronic structure of Cu100− x Zr x MGs revealed that the density of states (DOS) at Fermi level of Cu100− x Zr x metallic glass is mainly inherited from the Zr component. Abstract: The electronic structure of Cu100− x Zr x ( x  = 40,  50,  60) metallic glasses was investigated by ultraviolet photoelectron spectroscopy and X-ray photoemission spectroscopy, the valence band spectra of these alloys were analyzed by a large shift of the Cu d -band peaks to higher binding energies upon increasing Cu content. Photoemission experiments and first-principles calculations prove that the values of density of states at Fermi level of Cu100− x Zr x metallic glasses are mainly dominated by Zr rather than Cu. This work will enlighten further research on understanding the inheritance of metallic glasses and designing new metallic glasses with unique properties.